2010
DOI: 10.1007/s00264-010-1185-3
|View full text |Cite
|
Sign up to set email alerts
|

Nine years follow-up of 100 ceramic-on-ceramic total hip arthroplasty

Abstract: The aim of this study was to evaluate the first 100 cementless ceramic-on-ceramic total hip arthroplasty (THA) performed at our institution with more than nine years of follow-up. Clinical evaluation was performed using Harris hip score. Radiological evaluation was performed by two surgeons. Four patients were lost to follow-up. Harris hip score significantly improved at latest follow-up. Radiological analysis showed calcar osteolysis for 75 patients and one cup loosening. One patient required a revision five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…The low incidence of osteolysis in our patients with ceramic bearings is similar to recent reports [26-29, 32, 33]. Chevoillotte et al found no osteolysis at 8.8 years, whereas Kress et al reported 1% at 10.5 years [5,26] (Table 6).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The low incidence of osteolysis in our patients with ceramic bearings is similar to recent reports [26-29, 32, 33]. Chevoillotte et al found no osteolysis at 8.8 years, whereas Kress et al reported 1% at 10.5 years [5,26] (Table 6).…”
Section: Discussionsupporting
confidence: 77%
“…The incidence of squeaking in this ceramic study group is 1% and similar to recent reports [5, 26-28, 32, 33]. Chevoillotte et al [5] reported a 6% incidence of squeaking, whereas Park et al [33] at 9.6 years and Lewis et al [28] at 8 years reported 0%. The low incidence in our study is believed to be related to the more rigid stem design and metallurgy used in our ceramic cohorts.…”
Section: Discussionsupporting
confidence: 72%
“…The incidence of squeaking in the current study was similar to those reported in other recent studies. [34][35][36] In the current study, radiographic evidence of osteolysis was detected in 3 hips in the COP group and was absent in the COC group. The low incidence of osteolysis in patients with ceramic bearings was also similar to recent reports.…”
Section: A B Csupporting
confidence: 44%
“…The lack of these complications could be due to several features of the SuperPath technique including: a reduced need for soft tissue dissection with electrocautery; a lack of need to cut muscles or tendons; and the reduced need for transfusions, which have been previously linked to an increased incidence of surgical site infections [5]. The dislocation rate (0.8 %) was also decreased from those reported in some recent THA studies (2.9-6.0 %) and could help to further explain the reduced readmission rate [6][7][8].…”
Section: Thirty-day Readmission Ratementioning
confidence: 57%